New Tetramic Acid Derivatives From the Deep-Sea-Derived Fungus Penicillium sp. SCSIO06868 With SARS-CoV-2 Mpro Inhibitory Activity Evaluation - Pang, Xiaoyan; Chen, Weihao; Wang, Xin; Zhou, Xuefeng; Yang, Bin; Tian, Xinpeng; Wang, Junfeng; Xu, Shihai; Liu, Yonghong (Frontiers in Microbiology, 2021)
Three new tetramic acid derivatives (1–3) and a new polyketide (4) along with eight known compounds (5–12) were isolated from cultures of the deep-sea-derived fungus Penicillium sp. SCSIO06868. Four new structures were elucidated by analysis of 1D/2D NMR data and HRESIMS. Their absolute configurations were established by X-ray crystallography analysis and comparison of the experimental and reported ECD values or specific optical rotation. Compound 3 exhibited potent selective inhibitory activities against Staphylococcus aureus and methicillin-resistant S. aureus with MIC values of both 2.5 μg/mL. Also, compound 3 showed weak antiviral activity against SARS-CoV-2 main protease, which was responsible for the COVID-19 pandemic.